Malaria and Geohelminthiasis Coinfections in Expectant Women: Effect on Maternal Health and Birth Outcomes in a Malaria Endemic Region in Kenya - Wekesa Antony Wanyonyi; Chrispinus Siteti Mulambalah; David H. Mulama; Elizabeth Omukunda; Darwin Injete Siteti (Journal of Parasitology Research)
Geohelminthiasis and malaria coinfections in pregnancy are common in sub-Saharan Africa. The consequences of the disease combination on maternal health and birth outcomes are poorly understood. For a better understanding of this coinfection in expectant mothers, a cross-sectional study was carried out to evaluate the effect of the coinfection on maternal health and birth outcomes in expectant mothers in Bungoma County, Kenya. To collect data on malaria and maternal haematological parameters, blood samples were obtained from 750 participants aged 18-49 years and analyzed. Haemoglobin and eosinophils levels were determined by coulter counter while malaria parasitemia levels and red blood cell morphology were assessed by preparing and observing blood smears under the microscope. Fresh stool samples were collected and processed for identification and quantification of geohelminths species using Kato-Katz. Harada Mori technique was used to increase chances of detecting hookworms and Strongyloides infections. Neonate’s health was evaluated based on the appearance, pulse, grimace, activity, and respiration (APGAR) scale. Parasites identified were Plasmodium falciparum, P. malariae, P. ovale, Ascaris lumbricoides, Necator americanus, Enterobius vermicularis, and Schistosoma mansoni. The prevalence of geohelminths, malaria parasites, and coinfection was 24.7%, 21.6%, and 6.8%, respectively. Those coinfected with geohelminths and malaria parasites were four times likely to have anaemia (OR 4.137; 95% CI 2.088-8.195; P=0.001) compared with those infected with geohelminths or malaria parasites alone (OR 0.505; 95% CI 0.360-0.709; P=0.001 and OR 0.274; 95%CI 0.187-0.402 P=0.001, respectively). The odds of having preterm deliveries (OR 6.896; 95% CI 1.755-27.101; P=0.006) and still births (OR 3.701; 95% CI 1.008-13.579 P< 0.048) were greater in those coinfected than in those infected with either geohelminths or malaria parasites. Geohelminths and malaria coinfections were prevalent among study participants; consequently the risk of maternal anaemia, preterm deliveries, and still births were high. Routine screening and prompt treatment during antenatal visits should be encouraged to mitigate the adverse consequences associated with the coinfections.